Point of Arrival: Cranbrook Educational Community - Juhani Pallasmaa (Oz, 1998)
The proposed arrival plaza, "Point of Arrival," creates a visual and symbolic termination for the new entrance road to the center of the Cranbrook Educational Community. The concept integrates aspects of landscape architecture, sculpture, architectural design and a scientific instrument.